Satisfaction with indoor environmental quality in BREEAM and non-BREEAM certified office buildings - Altomonte, Sergio; Saadouni, Sara; Kent, Michael G.; Schiavon, Stefano (Taylor & Francis, 2017)
This paper presents preliminary analysis of occupant satisfaction with indoor environmental quality in Building Research Establishment Environmental Assessment Method (BREEAM) and non-BREEAM certified offices in the UK. Results from cross-sectional questionnaires (N = 121) showed that BREEAM certification per se did not seem to substantively influence building and workspace satisfaction. Conversely, occupants of BREEAM offices tended to be less satisfied with air quality and visual privacy than users of non-BREEAM buildings. Lower satisfaction was also detected in BREEAM offices for occupants having spent over 24 months in their building, and for users working in open-plan spaces. To interpret these findings, a methodology for data analysis was adopted whereas responses to point-in-time surveys (N = 82) were paired with environmental measurements. Broadening the perspective for appraising occupants’ perceptions, these combined techniques led to conclude that certification schemes should balance criteria addressing energy performance with design solutions considerate of issues of privacy, proxemics and perceived control over the qualities of the indoor environment.